2019
DOI: 10.1111/anae.14819
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of out‐of‐hours working and fatigue in consultants in anaesthesia and paediatric intensive care in the UK and Ireland

Abstract: The tragic death of an anaesthetic trainee driving home after a series of night shifts prompted a national survey of fatigue in trainee anaesthetists. This indicated that fatigue was widespread, with significant impact on trainees' health and well-being. Consultants deliver an increasing proportion of patient care resulting in long periods of continuous daytime duty and overnight on-call work, so we wished to investigate their experience of out-of-hours working and the causes and impact of work-related fatigue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 15 publications
(18 reference statements)
1
34
0
Order By: Relevance
“…Multiple studies among doctors found that prevalence of fatigue range from 28% to 91%. [12][13][14][15][16][17][18] The majority of them were experiencing high and frequent fatigue 17 18 with low and moderate intershift recovery. 19 These findings are not surprising as a doctor's Strengths and limitations of this study ► Multicentre study involving seven core clinical disciplines from seven tertiary public hospitals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies among doctors found that prevalence of fatigue range from 28% to 91%. [12][13][14][15][16][17][18] The majority of them were experiencing high and frequent fatigue 17 18 with low and moderate intershift recovery. 19 These findings are not surprising as a doctor's Strengths and limitations of this study ► Multicentre study involving seven core clinical disciplines from seven tertiary public hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous studies related to work hours and fatigue, [12][13][14][15][16][17][18][19][20][21] there is limited study specifically on acute fatigue, chronic fatigue and intershift recovery as well as their association with work-related activities during non-work time among doctors. To date, no similar study has been done in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…More than 300 million people need to undergo surgery each year all over the world [1], and over 70% of them got no access to safe, affordable anesthesia or surgical care [2], and the severe de ciency of global anesthesia workforce was one of the causes of this phenomenon [3]. The lack of rst-line doctors also led to work overload and more night shifts, which disturbed the biological rhythm and caused major stress and depression [4][5][6][7]. Exposed to long working hours, work overload, chronic sleep deprivation, need for sustained vigilance, continuous noise pollution and even the patients' halitosis [8], and contamination risk of COVID-19 [9], anesthesiologists are forced to bear huge job stress [10][11][12][13], which further cause anxiety, depression, sleep disturbances, memory and attention disturbance, nightmare, need for medication and so on [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, McClelland et al. provide data on self‐reported fatigue in a large cohort (n = 3847) of anaesthetic consultants and paediatric intensivists in the UK and Republic of Ireland . Although much has been written on fatigue in junior doctors and trainees, this is one of the first studies to report systematically on working time arrangements and self‐reported fatigue and well‐being in senior medical staff.…”
mentioning
confidence: 99%